Exploring a conceptual model, based on the combined effects of entrepreneurial leadership, market orientation and relationship marketing orientation on South Africa's small tourism business performance - H. J.C. Van Zyl; B. Mathur-Helm (South African Journal of Business Management, 2007)
This article explores the relationships between entrepreneurial leadership, market orientation and relationship marketing orientation and South Africa's Small tourism business performance. The entrepreneurial leadership construct is a product of the fusion of entrepreneurship and leadership constructs. This article firstly explores the relationship of entrepreneurial leadership as an antecedent to the blend of market orientation and relationship marketing orientation on small tourism performance, and secondly the relationship of the combined effects of entrepreneurial leadership, market orientation and relationship marketing orientation on small tourism business performance. It is a descriptive and theoretical article, and thus secondary data from previous studies are used as comparative analysis for examination and discussion. The findings indicate that there is a relationship between the identified constructs. However, the exact nature and extent of these relationships need to be further investigated.
Keywords: 650